Concerns of HIV-positive migrant workers in COVID-19 pandemic: A call for action - Ahmed, Ali; Dujaili, Juman; Sandhu, Anisha Kaur; Hashmi, Furqan Khurshid (Journal of global health, 2020)
[...]they continue to work, exposing themselves and others to risk [4]. [...]they face increasing difficulties in earning or receiving sufficient funds to afford ART medication [4,9]. Ensuring a migrants’ good health is critical for the countries in which they originate from and move to [10] However, reports globally show that migrants are often subject to health inequalities due to lack of access to adequate health care as a result of neglect, exclusion, discrimination, unfavourable employment conditions causing ill health, inadequate living conditions, financial constraints or lack of appropriate legal status [10].